Identification of Lüders bands using digital image correlation - Brlić, Tin; Debruyne, Dimitri; Lava, Pascal; Rešković, Stoja; Jandrlić, Ivan (2019)
This paper presents the characterization of Lüders bands by digital image correlation on niobium microalloyed steel during a static tensile testing. Digital image correlation with the qualitative and quantitative analysis of the Lüders bands on the microalloyed steel was proved as a very precise and suitable method for determining the strain amount in the deformation zone. In this research was determined that the strain amount is the highest in the area behind the Lüders band front and the lowest in the area in front of the Lüders band.
Bibliografija: 12 jed.
Abstract.
Keywords: Čelik -- Mikrolegirani čelik -- Naprezanje -- Lüderova linija -- Korelacija digitalne slike